Identification of Factors Associated with Medication Adherence in Renal Transplant Patients: An Integrative Literature Review - Martins Costa, Letícia (2023)
Objective: To identify factors associated with medication adherence in kidney transplant patients, showing the factors that contribute to increased and decreased adherence. Methods: A literature review was performed, searching the Medline Complete, Academic Search Premier, Embase and CINAHL databases. Rayyan was used for job management. Results: Of the 1,859 works initially identified, 36 articles were included in this research. All studies involved adult patients, usually with a mean age between 40 and 50 years. Men were the majority of patients in virtually every study. Most transplant patients had been transplanted for more than one year. Adherence was measured in most studies using validated and widely used instruments, such as The Basel Assessment of Adherence to Immunosuppressive Medication Scale (Baasis) and the Adherence to Immunosuppressive Therapy  Scale (ITAS). Other scales used for other diseases were also adopted, such as the Morisky instrument, used in versions with four or eight questions. Adherence values were quite distinct, ranging from very low values such as 10.8 and 16.9%, to very high values such as 90.8 or 94.5%. Among the factors that increase adherence are higher life satisfaction rate; better perception of medications; support from doctors; social support; longer waiting time on the transplant list; and better kidney function results. Among the factors that reduce medication adherence are: having a work contract; daytime sleepiness; palliative type of coping; less autonomy; financial problems; have stress; change of routine; less knowledge and literacy in health; adverse events to immunosuppressants; beliefs and concerns about immunosuppressants; lower belief in self-efficacy; and intrinsic religiosity. In addition, there were factors in which there is divergence in the literature regarding the influence on adherence, such as gender, age, income and time since transplantation. Conclusion: This study demonstrated that several modifiable and non-modifiable factors contribute to medication adherence, which demonstrates the importance of these findings for the care of kidney transplant patients.